2015
DOI: 10.4236/ojo.2015.57027
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Knee Joint Range of Motion after Stable Fixation of Tibial Plateau Fractures

Abstract: The purpose of this study was to evaluate factors that affect initiation of early postoperative range of motion (ROM) rehabilitation and to investigate whether the postoperative ROM and clinical outcomes were affected by initiation of early ROM, immobilization and other factors. We conducted a retrospective analysis of tibial plateau fractures treated using stable internal fixation between December 2003 and June 2007. The resulting degree of flexion and Rasmussen Clinical and Radiographic Scores were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
(34 reference statements)
3
7
0
Order By: Relevance
“…The reason for his low KOOS score was mainly due to poor motivation, social support and poor compliance to physiotherapy. All of our patient unable to achieve full knee flexion which correspond to the study by Arslan A et al where despite of immediate range of motion after stable internal fixation still unable to achieve full range of motion (6). Similar result was also reported by IR Ranatunga et all treated his patients with tibia plateau fractures using illizarov external fixator (14).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The reason for his low KOOS score was mainly due to poor motivation, social support and poor compliance to physiotherapy. All of our patient unable to achieve full knee flexion which correspond to the study by Arslan A et al where despite of immediate range of motion after stable internal fixation still unable to achieve full range of motion (6). Similar result was also reported by IR Ranatunga et all treated his patients with tibia plateau fractures using illizarov external fixator (14).…”
Section: Discussionsupporting
confidence: 89%
“…All of our patients have less than 5mm of condylar widening and less than 10 degree of Varus/Valgus angulation. Our outcome of radiological assessment are comparable to other studies using IEF or internal implants (5,6). Mao et al reported there is no difference in the radiological score when assessment was done at 3 months and 12 months (13).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of these fractures comprises around 1.2 percent of all fractures and is often higher among young individuals who have had high-energy trauma. 3 Most older people who have had low-energy trauma are also affected by them. 3 According to the Schatzker classification, there are six different types of tibial plateau fractures: lateral plateau fractures without depression (type I), lateral plateau fractures with depression (type II), compression fractures of the lateral or central plateaus (type IIIA or IIIB), medial plateau fractures (type IV), bicondylar plateau fractures (type V), and plateau fractures with diaphyseal discontinuity (type VI).…”
Section: Introductionmentioning
confidence: 99%